An Overview of Family Functioning in Parents with Adolescent Children in West Java - Mulya, Adelse Prima; Yamin, Ahmad; Purnama, Dadang; Suhenda, Dadang; Winyarti, Angela Sri Melani (Indonesian Journal of Global Health Research, 2025)
Adolescent health risk behaviors often occur due to the lack of control and supervision of family functions in Indonesia. Family plays an important role in adolescent health behavior. Objective: The purpose of this study is to see how the description of family functions in families with adolescent children. Method: This study is a quantitative study. The samples in this study were families (parents) who had adolescent children. The samples selected were families with adolescent children whose data had been recorded in the 2019 program performance and accountability survey (SKAP) system. With a total of 1999 respondents from West Java Province selected using stratified multistage sampling. The SKAP questionnaire type used a family function questionnaire with a Croanbach alpha value of 0.81. Data obtained from SKAP 2019 were analyzed descriptively quantitatively. Descriptive data will be presented in tabular form. Results: The results of the analysis showed that the family function was quite good as much as 70.2%. Conclusions: Family functions in families with adolescent children in West Java Province are mostly good enough. With the application of 8 optimal family functions in the family, it is expected to prevent health risk behavior in adolescents.